ANALISIS ATAS PENERAPAN PAJAK PENGHASILAN PASAL 22 (PENGADAAN BARANG) PADA PT. DANA TABUNGAN DAN ASURANSI PEGAWAI NEGERI (PERSERO) KANTOR CABANG MANADO - Bawon, Wulandari Safitri; Tinangon, Jantje J.; Tangkuman, Steven (Universitas Sam Ratulangi, 2018)
This study aims to determine the application of Income Tax Article 22 to Companies Savings Funds and Insurance of Employee Staff Manado Branch Office and find out whether the application has been in accordance with Regulation of the Minister of Finance No. 34 / PMK.010 / 2017. The type of research used is qualitative research using descriptive analysis technique. The results showed that the calculation used a tariff of 1.5% and paid using electronic SSP to the perception bank appointed by the Minister of Finance. And reporting is done using manual SPT and report it to Tax Office. The calculation, deposits, and reporting of Income Tax Article 22 is not fully in accordance with Regulation of the Minister of Finance No. 34 / PMK.010 / 2017 due to negligence in accounting that resulted in overpayment, and from the company does not issue Tax Assessment Letter More Pay (SKPLB) for SPT correction. Keywords : income tax, procurement, calculation, deposits, reporting